Essential Role for the Myotubularin-related Phosphatase Ymr1p and the Synaptojanin-like Phosphatases Sjl2p and Sjl3p in Regulation of Phosphatidylinositol 3-Phosphate in Yeast - Parrish, William R. (The American Society for Cell Biology, 2004)
The requirement of Vps34p, the sole phosphatidylinositol (PI) 3-kinase in Saccharomyces cerevisiae, for protein sorting to the vacuole in yeast has exemplified the essential role for phosphoinositides, phosphorylated derivatives of PI, in membrane trafficking. To better understand mechanisms that regulate PI 3-phosphate [PI(3)P]-mediated signaling, the role of the yeast myotubularin-related PI(3)P phosphatase Ymr1p was investigated. We found that Ymr1p and the synaptojanin-like phosphatase Sjl3p function as key regulators of the localization and levels of PI(3)P. Our data indicated that the ymr1Δ sjl3Δ double mutant aberrantly accumulated PI(3)P and demonstrated a steady-state redistribution of this lipid that leads to enrichment on the vacuolar membrane. This resulted in vacuole protein sorting defects, vacuolar fragmentation, and the misregulation of PI(3)P-specific effectors. Triple deletion of YMR1, SJL2, and SJL3 was lethal, suggesting an essential requirement for phosphatase-mediated PI(3)P regulation. Consistent with this, growth was restored to a ymr1Δ sjl2Δ sjl3Δ triple mutant by a PI(3)P-targeted Sac1p domain chimera (GFP-Sac1ΔC-FYVE(EEA1)) that returned PI(3)P to levels comparable with wild-type cells. Together, this study demonstrated that Ymr1p, a myotubularin phosphatase family member, functions in the control of PI(3)P-dependent signaling and the maintenance of endosomal system integrity. In addition, this work defined an essential overlapping role for lipid phosphatases in the regulation of 3′ phosphoinositides in yeast.